Some virtue ethics implications from Aristotelian and Confucian perspectives on family and business - Sison, Alejo G. (Journal of business ethics, 2020)
Not only individuals and firms, but also families engage in business as a social activity and this is true beyond the case of family businesses. Cultural differences in the way families are construed might influence the way they do business. There are different types of families, and among these are those described by Aristotelian and Confucian traditions, representing the West and the East respectively. The literature on virtue in business has been dominated by a Western—mainly Aristotelian—tradition (Ferrero and Sison in Bus Ethics Eur Rev 30(1): 8-24, 2014), neglecting the role of the family and focusing on the individual. In this paper, we seek to fill this gap by explaining differences and similarities in the normative evaluation of certain family-related business attitudes and practices, in light of Confucian and Aristotelian virtue ethics standards. After comparing the structure, organization and dynamics of Aristotelian and Confucian families, we shall draw some inferences regarding “virtuous” or excellent business practices—such as nepotism, bribery, gift-giving and guanxi and attitudes—on codified rules or written norms. For this analysis we shall make use of Aristotelian and Confucian ethical accounts as well as inputs from Family Science applied to organizations, which provides conceptual categories to compare the two traditions. Thus we hope to contribute not only to the comparative study of Aristotelian and Confucian virtue ethics in business, but also to the understanding of the distinctive role of families, raising cultural awareness for what may be considered virtuous business practices according to the Aristotelian and Confucian traditions.